Estudo de Análise do ciclo de vida aplicado à residência unifamiliar com foco em eco-análises e diagnósticos de impactos ambientais - Souza, Cássia Rafaela Brum (2025)
The construction sector has a positive and significant impact on the local enviroment and the surrounding region, resulting from its direct and indirects activities, and emerges as one os the most prominent and influential economic activities globally. In Brazil, the civil construction sector is experiencing significant growth and the increase in demand for construction materials is directly linked to the increase in consumption os raw materials qnd energy, especially during the extraction, processing and trasnsportation stages. There is an increasing urgency to minimize environmental impacts is favor os sustainability in the cinstruction industry. This study seeks to present the main waste generated by the construction sector, enumerating the impacts they generate, through Life Cycle Analysis (LCA) applied in a single-family home, analyzing the environmental effects of waste materials in the sector of construction: aluminium, steel, cement, ceramics and wood, cost-benefit comparison, applying the concept os sustainability to the supply chains os these materials and theis life cycles, aiming to assist in environmental decision-making and contribute to the management os the life cycle of a construction. “One square meter” was adopted as the functional unit to compare the same archutectural layout os the residence using different construction materials for the same function. The system boundary in this study follows the classification: “from the cradle to the grave”, the values obtained were 1,07E5 KgCO₂eq, equivalent to 564,82 KgCO₂eq/m²of emissions per square meter in the current scenario and 6,32E4 KgCO₂eq, equivalent to 333,61 KgCO₂eq/m² of emissions per square meter in the constrast scenario. In resource use, 1,21E6 MJ total was obtained for the current scenario, resulting in 6.387,24 MJ/m² total, and in the equivalent to 9,35E5 MJ total, reaching the value of 4.935,59 MJ/m². In the cost-benefit comparison, the sustainable scenario presented values 80% higher than the current scenario. "This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001"